DR-70: A promising biomarker for the detection of lung cancer - Özgül, Güler; Koç, Aysu Sinem; Turan, Demet; Küçük, Suat Hayri; Özsoy, Şule; Baydili, Kürşad Nuri; Güler, Eray Metin; Özgül, Mehmet Akif; Eğri Kansu, Zeynep; Seyhan, Ekrem Cengiz (Verduci Publisher, 2021)
Objective: Lung cancer (LC) is characterized by an aggressive phenotype with a high mortality rate, early metastasis, and proliferation rate. Treatment options and prognosis differ significantly at each stage. Despite the availability of multiple imaging studies and invasive procedures, the disorder is diagnosed at an advanced stage. Therefore, it is essential to find biomarkers for the early detection of LC. Patients and Methods: Between 2018 and 2020, 73 LC and 71 control with the same demographic characteristics were included in our study. DR-70 level was measured by a photometric method in serum samples taken from all subjects. Results: A total of 144 subjects (110 male, 34 female) was included in the study. DR-70 levels in the LC group (2.53 +/- 2.64 mu g/mL) were found to be statistically significantly higher than the control group (0.56 +/- 1.23 mu g/mL). Clinical sensitivity and specificity of DR-70 for LC were found to be 87.67% and 88.73%. Conclusions: The high sensitivity and specificity of DR-70 can be used as a biomarker for rapid diagnosis in patients with LC. Compared with other tumor biomarkers, DR-70 seems to have a better sensitivity and specificity in the diagnosis of LC.
Keywords: Lung Cancer; DR-70; Biomarker; Tumor Marker; Early Diagnosis